Reviews (New blackfriars, 1980)
Book reviewed in this article: The Eighth Century Phophets by B.W. Anderson Struggle And Fulfillment: The Inner Dynamics of Religion and Morality by Donald Evans. The Gospel According To St John, Vol II by Rudolf Schnackenburg, Tranelsted by C. Hastings, F. McDonagh, D. smith and R. Foley S. J. Herder's Groundwork Of Biblical Studies bt W. David Stacey,Epworth Press The Way Of The Preacher by Simon Tugwell O.P. darton, Longman & todd Historical Criticism and Theological Interpretation Of Scripture: Towards a Hermeneutics of Consent by Peter Stuhlmacher. Households Of God by David Parry O.S.B. The English Benedictines 1540–1688 by David Lunn. The English Benedictine Congregation by Dom Bernard Green. Benedict's Disciples, edited by David Hugh Farmer. Community And Abbot In The Rule Of Saint Benedict by Adalbert de. St Francis Of Assisi, Omnibus Of Sources ed. Marion A. Habig. The Nine Ways Of Prayer Of Saint Dominic, edited and translated by Simon Tugwell O P with lin drawings by Sheelagh Wilsden O. P.